The Relationship of the Dysmenorrhea a in Students with Learning Activities - Yoel Halitopo (Institute of Computer Science (IOCS), 2022)
Dysmenorrhea is one of the genetic complaints experienced by almost all women but with different levels of pain and different pain responses, so that it has an impact on daily activities such as social, study, work and daily activities. Learning activities are a process of teaching and learning activities that can be in the form of listening, asking questions, discussing, and writing. This study aims to determine the relationship between learning activities and the incidence of dysmenorrhea. The research method used is descriptive analytic research with cross sectional design. The research sample was 89 students of SMA Muhammadiyah Jayapura with a sampling technique using simple random sampling. Data were collected from respondents using questionnaires. The resultd showed that 85.5% of students who experienced moderate pain and 77.9% of students who experienced severe pain stated that they did not concentrate when doing learning activities. The results of the chi square test showed p value = 0.001, which means that there is a relationship between the incidence of dysmenorrhea and student learning activities. Dysmenorrhea can affect learning activities, this is supported by the duration of bleeding, pain during dysmenorrhea, and the intensity of dysmenorrhea.